Analisis Filtering Noise Menggunakan Metode Statistik Mean, Median pada Objek Citra Malam Hari - Rahmad, Rahmad (Politeknik Negeri Batam, 2017)
Image filtering is one part of image quality improvement, by smoothing and eliminating noise on the image, both linearly and non-linearly. The mean filter is one linear filtering that works by replacing the pixel value intensity with the average of the pixel value with its neighboring pixel values. While the median filter is one of the non-linear filtering that sort the intensity value of a pixel group, then replace the pixel value that is processed with its median value. This study studied noise reduction techniques using the mean and median filter method, to reduce the noise subsequently conducted in a trial of multiple color images with 30 previously selected image seals, Test image is given the noise of Salt & Pepper shaped like black spots and White on the image to reduce the noise is required method of noise filtering using median and mean filter. Then analyzed the performance qualitatively by comparing the image output filter, image bernoise and original image by naked eye. Quantitatively measured through PSNR, SNR and MSE values. Testing more in depth on the performance of this filter by finding the value of the difference between each value of PSNR, SNR and MSE and get good results. The difference is in the value of PSNR, SNR and MSE and the difference that has been obtained through filtering noise. It is concluded that good noise filtering using median filter method mean method is not good to be used in testing noise filtering on image.
Analysis of Filtering Noise Using Statistical Methods The Mean, The Median on The Object The Image of Night
Keywords: Teknik Informatika; Multimedia & Jaringan; Ilmu Komputer, Pengetahuan, Sistem; Analysis; Filtering; Statistical Methods